Fisheries management, the ecosystem approach, regionalisation and the elephants in the room. (October 2015) - van Hoof, Luc
Abstract: Many definitions of the ecosystem approach circulate, the common denominator being the system approach which seeks to take the entirety of a marine ecosystem into consideration. As marine ecosystems cover large geographical areas this approach calls for cooperation between the riparian states. This has being acknowledged in EU policies such as the Marine Strategy Framework Directive and the Marine Spatial Planning Directive. Yet implementing the ecosystem approach in practise runs into some operationalisation issues such as the position of regional cooperation between Member States vis a vis the treaty of the European Union; the positioning of the ecosystem approach between fisheries management and the Marine Strategy Framework Directive; the problem of stakeholder involvement and the balancing of ecological and economic concerns; the tension of the need for relative stability and the introduction of possible new models for organising regional cooperation. These issues appear to be like elephants in the room: obvious issues related to the need for regionalisation which apparently remain undiscussed. In this article, based on analyses within a number of European projects and discussions with relevant actors, the needed discussion on how to organise the management of human activities at the appropriate geo-political level matching the scale of the ecosystem, hence institutionalising marine management at the regional level, is initiated.